Enterprise Architecture Planning Information System at Bus Rental Service Company - STT, Latjuba Sofyana; Yunitasari, Yessi; Budi, Belca Setya (IC-ITECHS, 2024)
In increasing customer satisfaction, convenience and improving the quality of the company. The company engaged in bus rental services is PT. Transaba wants to have a digital platform and an integrated management system in the Company. One way is to do enterprise architecture planning to find out what systems/applications are urgent to create. The EAP framework provides the direction desired by the Company with its stages, including planning initiation, business modeling, current systems and technologies, data architecture and application architecture, and technology architecture. In this planning, the Company's directions and guidance regarding what must be done first to achieve the objectives, namely Procurement and installation of infrastructure, Customer Management System, Reservation management system, Scheduling and route system and Human Resources Training